(untitled) (International Journal of Mathematics and Physics, 2022)
This article presents innovative development of the system for the remote activity implementation. It’s all about from remote customer service to the company and private conferences for employees, online conferences, meetings, training, etc. This system refers to devices for implementing the employees’ remote production activities of the enterprise, to devices for organizing and managing the business processes. The developed system may be used without restrictions. The most important particularity of this useful system is the opportunity to add various features depending on the demand for a separate enterprise, upon that having saved a range of using the already existing opportunities. By applying this system, it is possible to increase by several times the level of the information and communication technologies usage for enterprises. The developed data device essentially allows economizing various resources on data transmission and storage. Besides, the requirements to the infrastructure of the enterprise may be used either by browsers or mobile devices, upon that by increasing the efficiency of analysis and the agility of making production decisions. Research and analysis of fault tolerance, applicability of modern IT technologies to increase the efficiency of enterprise digitalization have been carried out